(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
In the article the essence of sensory education in the formation of a child, the idea of an individual approach to each child, respect for him as a person, educating him from the spiritual and moral side, training in accordance with the interests and needs of the child is expressed.